STUDY OF BEE HONEY OF THE SPECIES Apis mellífera FROM NORTHEAST PARÁ (REMUNOM, 2024)
Honey is a natural product produced by bees through the nectar and secretions released by plants,with its production being carried out by honeybees, with emphasis on the species Apis mellífera. Thepresent work aimed to evaluate honeys of the A. mellífera species produced by beekeepers from sixmunicipalities in the Northeast of Pará, in physical-chemical terms and through multivariate statisticalmethods. The samples were collected in the municipalities of Tracuateua, São Miguel do Guamá,Aurora do Pará, Ourém, Santa Maria do Pará and Augusto Corrêa. Twelve variables were tested(electrical conductivity (EC), pH, viscosity, total insoluble solids (SIT), total soluble solids (TSS),density, moisture, turbidity, color, acidity, reducing sugars (AR) and ash). The results suggested thatmost samples agreed with the physical-chemical values stipulated by both national and international legislation, except for the variables moisture, air, ash and SIT, in which the latter presented valuesabove the legislation for all municipalities, suggesting product contamination. Through HCA and PCAit was possible to confirm the discrimination of variables according to the location of the samples,functioning as a resource to classify honeys according to their location and, consequently,contributing to their quality control.